Causes and therapeutic management of infertility in abandoned cows of Himachal Pradesh - SHARMA, ROHIT; SINGH, MADHUMEET; KUMAR, PRAVESH; SHARMA, AKSHAY (The Indian Journal of Animal Sciences, 2019)
The present study was carried out with an objective of examining the reproductive status of abandoned cows kept in 18 goshalas of Himachal Pradesh. Overall 321 abandoned cows were diagnosed with 402 reproductive ailments (few of them with multifactor etiology). Amongst the genital tract ailments in abandoned cows, a very high incidence, i.e. 50%, of reproductive disorders was associated with injuries/ technical errors (endometritis, cervical disorders, affections of fallopian tubes and adnexa) of which only 12.75% were treatable. However, 38.80% incidence of managemental/ functional problems (true anestrus and silent estrus) was found and a higher post treatment recovery rate was recorded. This can be attributed to the faulty AI technique, inefficient inseminators or inadequate training on AI. Overall, 22.86% abandoned cows having various reproductive ailments conceived following different therapeutic regimes.